Reading Al-Azhar's Interpretation of Al-Baqarah: 177 and 272 through a Marxist Hermeneutical Lens - Mubarok, Achmad Sofiyul; Damayanti, Natasya Alvira; Murtadlo, Hasan Aly; Elmanaya, Nourelhuda (QiST: Journal of Quran and Tafseer Studies, 2025)
In general, Karl Marx's discussion is framed in socio-political aspects. However, Buya Hamka chose Karl Marx as an influential figure in the modern century and mentioned him in the Al-Azhar interpretation. This article was written to analyze Karl Marx's position in Buya Hamka's Al-Azhar interpretation. This research is framed qualitatively with a descriptive-analytical approach to realize primary data and reveal Hamka's argumentative description related to Karl Marx. This research is based on two primary sources, the Al-Azhar interpretation and research relevant to the discussion. To reveal the representation of Karl Marx in Surah Al-Baqarah verses 177 and 272, this study theoretically adopts Stuart Hall's theory of representation to comprehensively reveal the role and position of Karl Marx. Preliminary results show that at the reflective representation level, Marxism is often portrayed in mainstream media as a dangerous ideology. Also, at the intentional representation level, the political bias of the old order, which tended to be anti-communist, colored Hamka's interpretation and positioned Marx as its figurehead. And at the constructional representation level, Hamka compared Marxist teachings with the Islamic justice system. In this case, Hamka's interpretation shows the results of social and cultural construction in the anti-communist era. Ultimately, this study bridges the understanding of Karl Marx's socialism and Islamic social teachings with nuances of interpretation, as well as offering a critical study of non-Muslim figures who have made significant contributions to Islamic discourse.